2014
DOI: 10.15252/embr.201438923
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐15b promotes neurogenesis and inhibits neural progenitor proliferation by directly repressing TET3 during early neocortical development

Abstract: MicroRNAs (miRNAs) are important regulators of mouse brain development. However, their precise roles in this context remain to be elucidated. Through screening of expression profiles from a miRNA microarray and experimental analysis, we show here that miR-15b controls several aspects of cortical neurogenesis. miR-15b inhibits cortical neural progenitor cell (NPC) proliferation and promotes cell-cycle exit and neuronal differentiation. Additionally, miR-15b expression decreases the number of apical progenitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…In hepatocytes, miR-15b promotes hepatitis B virus (HBV) replication by directly targeting HNF1a, whereas HBV replication represses the expression of miR-15b (30). In addition, miR-15b is involved in the expansion and differentiation of neural progenitor cells through cooperation with TET3 (31). In this study, miR-15b was found to regulate JEVinduced inflammation.…”
mentioning
confidence: 70%
“…In hepatocytes, miR-15b promotes hepatitis B virus (HBV) replication by directly targeting HNF1a, whereas HBV replication represses the expression of miR-15b (30). In addition, miR-15b is involved in the expansion and differentiation of neural progenitor cells through cooperation with TET3 (31). In this study, miR-15b was found to regulate JEVinduced inflammation.…”
mentioning
confidence: 70%
“…We refer the reader to excellent recent reviews for a detailed discussion of miRNA function in adult neurogenesis (Luikart et al, 2012;Schouten et al, 2012) and focus our discussion here on embryonic neurogenesis -a period during which many miRNAs are enriched. Indeed, the global monitoring of miRNA expression during neurogenesis in vivo has identified timespecific (Barca-Mayo and De Pietri Tonelli, 2014;Lv et al, 2014;Miska et al, 2004;Nielsen et al, 2009;Yao et al, 2012), spatially restricted (ventral midline/midbrain dopaminergic progenitor pool) (Anderegg et al, 2013) or cell type-specific (Paridaen and Huttner, 2014;Ghosh et al, 2014) miRNAs, suggesting that different sets of miRNAs might be involved in neuronal versus glial differentiation. This is supported by the finding that 116 miRNAs (out of 351) are differentially expressed in primary cultures enriched for neurons, astrocytes, oligodendrocytes and microglia (Jovicic et al, 2013).…”
Section: Cell Fate Determinationmentioning
confidence: 99%
“…Additional miRNAs such as miR-20a/20b and miR-23 also negatively regulate cyclin D1 levels via direct 3′UTR interaction (Ghosh et al, 2014), and increased cyclin D1 activity leads to elevated miR-23 and decreased miR-20a/b expression levels; importantly, the inhibition of each of these miRNAs interferes with proper neuronal differentiation (Ghosh et al, 2014). Finally, it has been shown that another miRNA, miR-15b, inhibits cyclin D1 expression by regulating the methylation status of the cyclin D1 promoter via suppression of Tet methylcytosine dioxygenase 3 (TET3) mRNA translation (Lv et al, 2014). In summary, the Wnt signaling pathway provides an excellent example of a module that is concomitantly regulated by multiple miRNAs during neurogenesis.…”
Section: Neurogenesismentioning
confidence: 99%
“…Furthermore, miRNAs can also interplay with other epigenetic regulators and play a comprehensive role in regulating neurogenesis [133]. miR-15b inhibits demethylase activity of Tet3 and then reduces the expression of cyclin D1 [134]. As a result, miR-15b accelerates neurogenesis and inhibits NPC proliferation during mammalian corticogenesis [134].…”
Section: Ncrnas In Embryonic Neurogenesismentioning
confidence: 99%
“…miR-15b inhibits demethylase activity of Tet3 and then reduces the expression of cyclin D1 [134]. As a result, miR-15b accelerates neurogenesis and inhibits NPC proliferation during mammalian corticogenesis [134].…”
Section: Ncrnas In Embryonic Neurogenesismentioning
confidence: 99%